PEMANFAATAN AMPAS BIOETANOL DARI KULIT PISANG (Musa Sapientum) SEBAGAI BRIKET - Reny Nurainy; Sri Sumiyati; Endro Sutrisno (Jurnal Teknik Lingkungan, 2013)
ABSTRACTWith the energy crisis in Indonesia in recent years is due to the human need for fuel is increasing, while the supply of oil or natural gas is limited. This causes the cost of fuel energy. In addition to fuel oil and natural gas, timber when done randomly and in large quantities will interfere with the balance of the ecosystem or environmental sustainability. The purpose of this study was to obtain fuel briquettes from waste banana peel pulp bioethanol, as a substitute for fossil fuels. The study was conducted with a variable fixed briquette diameter 1 cm, height 5 cm and a total weight of 22 grams per briquet. While variable is the% change in the composition of the adhesive (25% and 50%) and the type of material that is Ampas bioethanol kepok banana peel and King. Response observed that color, calorific value, long burning fire and the resulting color. The results showed that% moisture content greatly affects the calorific value, long burning time. The calorific value of the greatest and most long ignition time obtained on treatment plantain because it produces a lower water content compared to banana pulp kepok. From the analysis that has been done can be concluded that the briquettes are in accordance with SNI.